Evaluation of Underground Water Quality in Terms of Irrigation Water in Tekirdağ Province - Ülviye Çebi (Turkish Journal of Agriculture: Food Science and Technology, 2020)
This study includes some deep underground well waters opened to supply the irrigation water in Tekirdağ province. The sampling was done from 22 wells in the irrigation season period. The parameters such as pH, EC, TDS, Na, Ca, Mg, K, Cl, HCO3, B, NO3-N, Sodium Absorption Ratio and Residual Sodium Carbonate parameters, which were significant in terms of irrigation water classification, were examined in the samplings. According to the results, it was determined that thirteen well waters were in medium salty and eight well waters were in high salty water classes. Besides, Na and HCO3 harms were determined in five and three well waters, respectively. In seven well waters, it was concluded that RCE values were over 2,5 me L-1 and these water were not suitable in the usage of irrigation. As a result of the evaluations in terms of the specific ions, it was determined that CL, B and NO3-N concentrations which were found in three, two and one wells respectively, could create damages in some crops. As a result of the evaluations in terms of salinity and SAR parameters, it was concluded that the usage of T5, T6, T8, T10, T13 and T14 well waters was undesirable and the usage of T9, T11, T12, T16, T17 and T21 well waters can be suggested by the provision of some special conditions (appropriate drainage conditions, appropriate plant selection, coarse textured soils).